Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1970
DOI: 10.1017/s0022172400042480
|View full text |Cite
|
Sign up to set email alerts
|

Further investigations on the airborne excretion of foot-and-mouth disease virus

Abstract: Calf thyroid tissue cultures were found to be the most sensitive system in detecting virus collected in a large volume air sampler from boxes, where cattle, sheep and pigs infected with A and C strains of foot-and-mouth disease (FMD) virus were housed. It was confirmed with all strains of FMD virus tested that pigs excreted the most virus followed by cattle and sheep, but there was variation between strains, the highest virus recoveries being obtained from animals infected with O(1) and C Noville viruses. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
1

Year Published

1970
1970
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 4 publications
3
65
0
1
Order By: Relevance
“…Swine in particular, being capable of replicating and shedding FMDV at high titer, have been implicated as an amplifying host in FMD outbreaks, 3,10 highlighting the value of swine herd surveillance. Low-virulence CSF represents yet another prominent threat to swine industries with the heightened potential for delayed detection in swine herds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Swine in particular, being capable of replicating and shedding FMDV at high titer, have been implicated as an amplifying host in FMD outbreaks, 3,10 highlighting the value of swine herd surveillance. Low-virulence CSF represents yet another prominent threat to swine industries with the heightened potential for delayed detection in swine herds.…”
Section: Discussionmentioning
confidence: 99%
“…Dilutions of viral purNA were preferred over the use of synthetic nucleic acid targets to permit analysis of sensitivity and specificity of target nucleic acid detection in the context of viral genomic nucleic acid and secondary structure motifs such as hairpins. For the relative analytical sensitivity analysis, each purNA pool consisted of purified nucleic acid from ASFV (Kimakia-64, 3 /mL) thus containing complete pathogen genomic sequences and also mimicking the presence of multiple pathogens in diagnostic samples. Dilutions were performed using pooled purified nucleic acid from OF collected from uninfected control swine to mimic diagnostic samples with potentially interfering host and environmental factors.…”
Section: Multiplex Rt-qpcr Linear Dynamic Range Relative Analytical mentioning
confidence: 99%
“…The types of animals, methods of infection, air sampling and virus assay of aerosols from infected animals have already been described (Sellers & Parker, 1969;Donaldson et at. 1970 …”
Section: Methodsmentioning
confidence: 99%
“…Of the 37 cases reported 23 were due to type 0, 13 to type C and 1 to type A virus. In a serological survey of workers exposed to FMD virus, Suhr Rasmussen (1968) and Wisniewski & Jankowska (1968) found that low titre antibodies to type 0 were the most prevalent followed by type C. In this connexion it is interesting to note that the highest yields of airborne virus were recovered from animals infected with 01 or C Noville strains of virus (Donaldson, et al 1970).…”
Section: Fmd and Man Removal Of Virus From Nosementioning
confidence: 97%
“…Foot-and-mouth disease (FMD) is most frequently transmitted by aerosol (Fogedby, Malmquist, Osteen & Johnson, 1960; Hyslop, 1965b;Sellers & Parker, 1969; Donaldson, Herniman, Parker & Sellers, 1970; Graves, McVicar, Sutmoller & Trautman, 1971). In cattle, virus can gain entrance through t-he upper or lower respiratory tracts or the eye, each of which has been shown to be susceptible J. W. MCVICAR AND P. SIUTMOLLER to experimental inoculation (Sutmoller, McVicar & (Cottral, 1968;Eskildsen, 1968;Sutmoller & McVicar, 1973).…”
Section: Introductionmentioning
confidence: 99%